Pengaruh Latihan High Intensity Interval Training (HIIT) Terhadap Kadar Triglierida Pada Atlet Lari Jarak Jauh Pasi Kota Malang - Dimas Pratama Putra; Rias Gesang Kinanti; Ardhiyanti Puspita Ratna (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
Triglycerides are fats carried by the lipoprotein system located in the blood, are the main cause of arterial diseases and are usually compared with cholesterol using lipoprotein electrophoresis. Triglycerides consist of glycerol linked to fatty acid groups. The High Intensity Interval Training method is a sport designed to increase metabolism and burn body fat so as to balance triglyceride levels in the body. This exercise is often included in training programs for long-distance runners. This study aims to obtain information about the effect of the High Intensity Interval Training (HIIT) exercise on the interval running model on triglyceride levels in PASI Athletes in Malang City. The research method and design used was an experiment in the form of the one group pretest-posttest design, namely recording the results of triglyceride levels before HIIT training and after HIIT training. This study involved 8 long-distance runners whose blood was taken from the cubital vein before the HIIT treatment. The design of this study was initiated by screening all research subjects according to predetermined inclusion criteria. And all subjects were instructed to fill out a willingness form (informed consent) then proceed with taking a blood sample before the HIIT exercise treatment of ± 10 µL. After taking blood, the HIIT training program is continued with an interval running model, namely by running fast for 2 minutes, then walking for 2 minutes, doing 10 repetitions. After completing the HIIT training treatment, all subjects took blood again as much as ± 10 µL. When all subjects' blood samples have been taken, it is followed by laboratory tests in the clinical pathology laboratory, Faculty of Medicine, Brawijaya University. The results of the study by conducting a paired sample T-test were used to analyze the data obtained with a significant (2-tailed) value of 0.938 greater than the p value of 0.05 (0.938> 0.05) indicating H0 was accepted and Ha was rejected which means that HIIT training has no significant effect on the leukocyte levels of PASI Athletes in Malang City. So it can be concluded that HIIT training has no effect on increasing leukocyte levels in PASI Athletes running long distances in Malang City. The conclusion in this study was that the HIIT training provided had no significant effect on the amount of triglycerides after and after exercise. Triglyceride levels in long-distance runners are at normal levels. This is because there has been regular practice given by the coach as preparation for the match.